Biomolecular interactions and binding dynamics of inhibitor arachidonic acid, with tyrosinase enzyme. Issue 4 (4th March 2023) - Shojazadeh, Tahereh; Zolghadr, Leila; JafarKhani, Saeed; Gharaghani, Sajjad; Farasat, Alireza; Piri, Hossein; Gheibi, Nematollah
Abstract: Hyperpigmentation is a disorder caused by increased melanin deposition and changes in skin pigmentation. Inhibition of tyrosinase activity contributes to the control of food browning and skin pigmentation diseases. The effects of arachidonic acid (AA) on tyrosinase activity were examined using different spectroscopy methods including UV-VIS spectrophotometry, fluorescence spectroscopy, circular dichroism (CD) differential scanning calorimetry, and molecular dynamics (MD) simulations. Based on the kinetic results, arachidonic acid showed mixed-type of inhibition with Ki = 4.7 µM. Fluorescence and CD studies showed changes of secondary and tertiary structures of enzyme and a reduction of α-helix* amino acids after its incubation with different concentrations of AA, which is also confirmed by DSSP analysis. In addition, differential scanning calorimetry (DSC) studies showed a decrease in thermodynamic stability of enzyme from Tm = 338.65k for sole enzyme after incubation with AA in comparison with complex enzyme with Tm= 334.26k, ΔH =7.52 kJ/mol, and ΔS = 0.15 kJ/mol k. Based on the theoretical methods, it was found that the interaction between enzyme and AA follows an electrostatic manner with ΔG = −8.314 kJ/mol and ΔH = −12.9 kJ/mol. The MD results showed the lowest flexibility in the complex amino acids and minimal fluctuations in AA interaction with tyrosinase in Residue 240 to 260 and 66 to 80. Thus, AA inhibitory and structural and thermodynamic instability of tyrosinase supported advantages of this fatty acid for prevention of medical hyperpigmentation. Therefore, it is a good candidate for cosmetic applications. Communicated by Ramaswamy H. Sarma Abstract : UF0001